Memory [videorecording (DVD)] - Neeson, Liam; Pearce, Guy, 1967-; Bellucci, Monica, 1968-; Atwal, Taj; Fearon, Ray; Stevenson, Ray, 1964-; Jaramillo, Antonio (Actor); De Bourg, Daniel; Williams, Scot; Stocker, Stella; Torres, Harold; Geeraerts, Jef (Universal, 2022)
When Alex, an expert assassin, refuses to complete a job for a dangerous criminal organization, he becomes a target. FBI agents and Mexican intelligence are brought in to investigate the trail of bodies, leading them closer to Alex. With the crime syndicate and FBI in hot pursuit, Alex has the skills to stay ahead, except for one thing: he is struggling with severe memory loss, affecting his every move. Alex must question his every action and whom he can ultimately trust.